Horseshoe tears in the retina after traumatic posterior vitreous detachment - Zorc, Stephen A.; Wilneff, Matthew; Shrier, Eric M. (Digital Journal of Ophthalmology, 2026)
A 70-year-old man with no known past ocular history presented to the Brooklyn Veterans Affairs Hospital after a fall from standing height with the chief complaint of flashing lights in his vision. Ultrawide-field Optomap imaging of the patient’s right eye demonstrated three large horseshoe retinal tears extending from 2:00 to 5:00 at the ora serrata. Persistent vitreous attachment to the peripheral retina, combined with the traumatic fall mechanism, produced the characteristic tear pattern. The contiguous inferior tears illustrate vitreous avulsion associated with traumatic retinal injury. These tears are a significant risk factor for rhegmatogenous retinal detachment due to liquefied vitreous accessing the subretinal space through the breaks. Horseshoe tears in the retina often result from posterior vitreous detachment, particularly in patients with risk factors such as myopia, trauma, and lattice degeneration. Timely identification of these tears is critical to preventing retinal detachment. Management may involve laser retinopexy to barricade the tear and prevent progression.